Simultaneous screening and quantification of aminoglycoside antibiotics in honey using mixed‐mode liquid chromatography with quadrupole time‐of‐flight mass spectroscopy with heated electrospray ionization. Issue 16 (16th July 2018) - Perkons, Ingus; Pugajeva, Iveta; Bartkevics, Vadims
Abstract: An analytical method based on liquid chromatography with quadrupole time‐of‐flight mass spectrometry has been developed for the simultaneous determination of six aminoglycoside antibiotics in honey. The sample pretreatment included extraction with aqueous trichloroacetic acid followed by solid‐phase extraction on Strata‐X polymeric reversed phase cartridges. Liquid chromatography separation was performed on an Obelisc R zwitterionic type mixed‐mode column. An ionBooster™ heated electrospray source was used and showed enhanced ionization efficiency in comparison to a conventional electrospray source. The observed signal enhancement ranged from 3‐ (neomycin) to 16‐fold (gentamicin C1). A data‐dependent mass spectrometry acquisition approach was employed, in which the full mass spectrometry dataset provided quantification and a scheduled precursor list was used to trigger an alternating data‐dependent acquisition of MS 2 spectra for confirmation purposes. The described method was validated in accordance to CD 2002/657/EC. Decision limit values were in the range 11.2–33.6 ng/g, and satisfactory performance characteristics were obtained for recovery (65–76%), repeatability (3.8–7.3%), and linearity (≥0.995). The method was applied to the analysis of 49 real honey samples from the country of Georgia. Streptomycin was detected in two samples at 117 and 35 ng/g, and gentamicin C1 was detected in one sample at 32 ng/g.